2015
DOI: 10.1108/ijcthr-08-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the economic value of night view of bridge using contingent valuation method: the case of South Korea’s Han-River bridge

Abstract: Purpose – The purpose of this paper is to estimate an individual’s probability of preservation of the night view of Han-River bridge tax using the contingent valuation method (CVM) and to present the effects of 4Es on experience economy theory. Design/methodology/approach – The on-site survey was conducted in the 11 district Han-River parks: Gwangnaru, Jamsil, Ttukseom, Jamwon, Banpo, Yeechon, Yeouido, Mangwon, Nanji, Ganseo and Yanghwa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…But surprisingly, the result of this study indicated that age has no significant effect on WTP or WTP amount. Few studies agreed with this result like (Loomis et al, 1996), while many other studies in the literature revealed that age has a significant impact on WTP like (Nam et al, 2014;Yang and Solgaard, 2015;Yung and Chan 2015;Sriwaranun et al, 2015). They believed that the older the respondents are, the higher is the probability for their WTP and WTP amount.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…But surprisingly, the result of this study indicated that age has no significant effect on WTP or WTP amount. Few studies agreed with this result like (Loomis et al, 1996), while many other studies in the literature revealed that age has a significant impact on WTP like (Nam et al, 2014;Yang and Solgaard, 2015;Yung and Chan 2015;Sriwaranun et al, 2015). They believed that the older the respondents are, the higher is the probability for their WTP and WTP amount.…”
Section: Discussionmentioning
confidence: 95%
“…Income level has a significant effect on both WTP and WTP amount. While few studies referred to income as an insignificant variable regarding WTP (Loomis et al, 1996;Yang, and Solgaard, 2015), many others proved that income is one of the most significant variables affecting respondents' WTP and WTP amount (Otegbulu, 2011;Nam et al, 2014;Gao et al, 2014;Sriwaranun et al, 2015). This means that the higher the income level, the higher the probability for respondents to have a WTP for the service in question.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations